Electrode material for lithium extraction and preparation method thereof
By forming a rare earth phosphate layer on the surface of the lithium-extracting electrode material and combining carbon coating, the problem of fast capacity decay and short service life in the alkaline solution is solved, which significantly improves the cycling performance of the electrode and the lithium-extracting efficiency, and reduces the overall cost.
Patent Information
- Application Number
- CN202411678988.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-14
AI Technical Summary
The lithium extraction electrode used in the prior art for alkaline solutions has problems such as fast capacity decay, difficulty in taking into account both the capacity retention rate and the lithium extraction rate, and short service life, resulting in a low overall lithium extraction efficiency and a significant increase in cost.
By forming a rare earth phosphate layer by in-situ coating on the surface of the electrode active material, and combining the carbon coating strategy, a three-layer sandwich structure with the electrode active material as the core and the rare earth phosphate layer and the carbon layer as the shell is built to improve the cyclic performance and conductivity of the electrode material.
It significantly improves the circulation performance of the lithium-extracting electrode, extends its service life, enhances the lithium-extracting efficiency, reduces the overall cost, and solves the problems of fast capacity attenuation and short service life.
Smart Images

Figure CN119615286A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium extraction from salt lakes, and in particular to an electrode material for lithium extraction and a preparation method thereof, a lithium extraction electrode and a lithium extraction system. Background Art
[0002] As one of the strategic mineral resources, lithium is a key raw material for the new energy industry chain. More than 80% of my country's lithium resources are found in salt lake brines. According to the chemical composition of the brine, salt lakes can be divided into chloride type, sulfate type and carbonate type. Carbonate brine generally has the characteristics of high lithium concentration, low magnesium-lithium ratio, large reserves and simple brine mining. However, due to the limitation of lithium extraction technology, the lithium carbonate output of domestic carbonate brine is less than 10,000 tons.
[0003] At present, the lithium extraction processes that can be used for carbonate brine mainly include: solar pond precipitation method, adsorption method, extraction method and electrochemical deintercalation method. Compared with other methods, the electrochemical deintercalation method can realize the insertion and removal of lithium by only turning on the power, and does not involve the use of acid, alkali and various toxic and harmful substances. It is a green and efficient lithium extraction technology. However, when the electrochemical deintercalation method is used to treat carbonate brine, the capacity of the lithium extraction electrode decays very quickly, resulting in a significant decrease in the lithium extraction capacity, which limits its industrial application. Summary of the invention
[0004] In view of the above analysis, the present invention aims to provide an electrode material for lithium extraction and a preparation method thereof, a lithium extraction electrode and a lithium extraction system, so as to solve at least one of the following problems existing in the lithium extraction electrode for alkaline solution in the prior art: (1) rapid capacity decay; (2) difficulty in balancing capacity retention and lithium extraction rate, and low overall lithium extraction efficiency; (3) short service life, and frequent replacement leads to a significant increase in overall cost.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for preparing an electrode material for lithium extraction, comprising the following steps: mixing an electrode active material with a rare earth salt solution, and forming a rare earth phosphate layer on the surface of the electrode active material by in-situ coating; the electrode active material comprises lithium iron phosphate and its doped derivatives.
[0007] Furthermore, after forming the rare earth phosphate layer, the method further comprises: mixing the electrode active material having the rare earth phosphate layer coated on the surface with a precursor solution containing a carbon source, and after solid-liquid separation, calcining the separated solid powder at a high temperature under the protection of an inert gas; or,
[0008] Before mixing the electrode active material with the rare earth salt solution, the method also includes: mixing the electrode active material with a precursor solution containing a carbon source, and after solid-liquid separation, high-temperature calcining the separated solid powder under the protection of an inert gas; then mixing the electrode active material having a surface coated with a carbon layer after high-temperature calcination with a rare earth salt solution, and forming a rare earth phosphate layer on the surface of the electrode active material coated with the carbon layer by in-situ coating.
[0009] Further, the particle size of the electrode active material powder is 0.5-6.0 μm, and the concentration of the rare earth salt solution is 0.02-3.5 mol / L;
[0010] According to the solid-liquid ratio α and mixing time t x The electrode active material is mixed with the rare earth salt solution, or the electrode active material coated with a carbon layer after high temperature calcination is mixed with the rare earth salt solution, the solid-liquid ratio α is 1: (5-20), and the mixing time t x 0.5-24h.
[0011] Further, the concentration of the precursor solution containing the carbon source is 0.02-4 mol / L; according to the solid-liquid ratio δ and the mixing time t c , the electrode active material is mixed with a precursor solution containing a carbon source, or the electrode active material coated with a rare earth phosphate layer is mixed with a precursor solution containing a carbon source, the solid-liquid ratio δ is 1: (5-20), and the mixing time t c 0.5-24h; and / or,
[0012] The temperature of high temperature calcination is 400-750°C, and the time of high temperature calcination is 2-8h.
[0013] Furthermore, the concentration of the rare earth salt solution is 0.2-2 mol / L, the solid-liquid ratio α is 1:(8-15), and the mixing time t x 0.5-6h.
[0014] Furthermore, the rare earth salt solution is an inorganic salt solution containing rare earth elements, and the inorganic salt solution is one or more of chloride, sulfate and nitrate; and / or,
[0015] The precursor solution containing the carbon source is a mixed solution of one or more of glucose, sucrose, dopamine, tannic acid and polyvinyl pyrrolidone.
[0016] Further, when the precursor solution containing the carbon source is a mixed solution of glucose and sucrose, the concentration of the mixed solution of glucose and sucrose is 1.0-4.0 mol / L; or,
[0017] When the precursor solution containing a carbon source is a dopamine solution, the concentration of the dopamine solution is 0.1-0.3 mol / L; or,
[0018] When the precursor solution containing the carbon source is a tannic acid solution, the concentration of the tannic acid solution is 0.2-1.0 mol / L; or,
[0019] When the precursor solution containing the carbon source is a polyvinyl pyrrolidone solution, the concentration of the polyvinyl pyrrolidone solution is 0.5-1.0 mol / L.
[0020] The present invention also provides an electrode material for lithium extraction, which is obtained by the preparation method as described above.
[0021] The present invention also provides a lithium extraction electrode, which is prepared using the above-mentioned electrode material; the lithium extraction electrode is mainly used for extracting lithium from salt lake brine, and the salt lake brine includes carbonate brine, chloride brine, and sulfate brine.
[0022] The present invention also provides a lithium extraction system, comprising an anode and a cathode, wherein the anode is an electrode prepared from the electrode material as described above, and the cathode is an electrode prepared from the electrode material as described above after a lithium removal treatment.
[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0024] (1) The present invention coats a layer of rare earth phosphate on the surface of the electrode active material particles by the method of "in-situ coating", which can significantly improve the cycle performance of the lithium extraction electrode (for example, the capacity retention rate after multiple charge and discharge). Specifically, compared with the method of "mixing rare earth oxides with electrode active materials and then high-temperature heat treatment", the "in-situ coating" method provided by the present invention can significantly improve the density and uniformity of the rare earth phosphate coating layer and the bonding strength between the rare earth phosphate coating layer and the electrode active material, which helps to give full play to the physical barrier effect of the rare earth phosphate coating layer, and to avoid the contact of the electrode active material with salt lake brine (for example, alkaline carbonate brine) to the maximum extent, thereby reducing the possibility of phase change, so that the rare earth phosphate coating layer can effectively resist and avoid the decomposition of the electrode active material in salt lake brine (for example, alkaline carbonate brine), and achieve the purpose of long-term stable lithium extraction electrode. Therefore, the method of in-situ coating of rare earth phosphate in the present invention has significant advantages in improving the cycle performance of the lithium extraction electrode, and can effectively solve the problem of fast capacity decay of the lithium extraction electrode used for alkaline solution in the prior art.
[0025] (2) Considering that the existing lithium extraction electrodes have the problem of being difficult to balance the capacity retention rate and the lithium extraction rate when treating salt lake brine, especially alkaline brine (e.g., carbonate type), the present invention prepares the electrode material for lithium extraction by combining the strategy of in-situ coating of rare earth phosphate with carbon coating, which can not only improve the cycle performance of the lithium extraction electrode, but also accelerate the lithium extraction rate by enhancing the conductivity of the lithium extraction electrode. Specifically, by combining the strategy of in-situ coating of rare earth phosphate with carbon coating, a three-layer sandwich structure with the electrode active material as the core and the rare earth phosphate layer and the carbon layer as the shell is constructed. This structure can protect the core electrode active material and provide good ion and electron transmission channels to balance better ion conductivity and electron conductivity, thereby improving the overall lithium extraction efficiency of the lithium extraction electrode, and ensuring the cycle stability of the lithium extraction electrode, so as to solve the problem that the lithium extraction electrode used for salt lake brine, especially alkaline brine (e.g., carbonate type) in the prior art is difficult to balance the capacity retention rate and the lithium extraction rate.
[0026] (3) The present invention prepares the electrode material for lithium extraction electrode by in-situ coating of rare earth phosphate combined with carbon coating, which can effectively reduce the corrosion of salt lake brine, especially alkaline brine (e.g. carbonate type) on lithium extraction electrode, enhance the structural integrity and thermal stability of lithium extraction electrode, and significantly extend its cycle life. Compared with the prior art, the preparation method provided by the present invention can significantly reduce the replacement frequency of lithium extraction electrode, thereby showing obvious advantages in reducing overall cost.
[0027] (4) The preparation method provided by the present invention realizes the coating of rare earth phosphate by in-situ phase transformation technology. This method is not only simple in process but also environmentally friendly, meeting the current needs of environmental protection and sustainable development. The promotion and application of this preparation method will help the application of electrochemical deintercalation method in lithium extraction from salt lake brine, especially alkaline brine (e.g. carbonate type), and promote its large-scale development.
[0028] (5) In some preferred embodiments, by further controlling the particle size of the electrode active material powder, the concentration of the rare earth salt solution, the concentration of the precursor solution containing the carbon source, the solid-liquid ratio, the process parameters during coating (such as mixing time, mixing method), and the process parameters of high-temperature calcination, it is beneficial to form a uniform and appropriately thick rare earth phosphate layer and carbon layer on the surface of the electrode active material particles, so as to better play their physical barrier role and conductivity improvement role, further enhance the cycle performance and lithium extraction efficiency of the electrode when extracting lithium from salt lake brine, especially alkaline brine (such as carbonate type), and further extend the service life of the electrode to reduce the overall cost.
[0029] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0031] Figure 1 The cycle capacity variation curves of the embodiments of the present invention and the comparative examples when extracting lithium from carbonate brine are shown;
[0032] Figure 2 The graph of lithium concentration variation of brine when extracting lithium from carbonate brine is shown in the examples of the present invention and the comparative examples;
[0033] Figure 3 The cycle capacity variation curves of the embodiments of the present invention and the comparative examples when extracting lithium from chloride-type brine are shown;
[0034] Figure 4 TEM images of the coated lithium iron phosphate surfaces obtained in the embodiments of the present invention and the comparative examples, (a) is a TEM image of the lithium iron phosphate surface coated with only a carbon layer in comparative example 1, and (b) is a TEM image of the three-layer structure of the lithium iron phosphate surface coated with lanthanum phosphate and a carbon layer in embodiment 2. DETAILED DESCRIPTION
[0035] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0036] Based on the basic characteristics of lithium extraction by electrochemical deintercalation, the inventors tested the adaptability of this lithium extraction technology (i.e., electrochemical deintercalation) in various types of salt lake brines, and found that this lithium extraction technology has a good lithium extraction effect in chloride and various types of sulfate brines, and the separation coefficient of lithium and metal cations is as high as tens or even hundreds. The electrode material still has a good capacity retention rate after hundreds of cycles. However, when the lithium extraction technology is used to treat carbonate brine, the capacity of the electrode material decays very quickly; after research and analysis, the inventors found that the rapid capacity decay is mainly due to the high pH value of carbonate brine (9-10), and the FePO4 electrode commonly used for lithium extraction is easy to phase change in alkaline solutions with pH>8.6 to generate Fe(OH)3 phase with lower solubility, which destroys the structure of the electrode material and leads to a decrease in lithium extraction capacity.
[0037] Based on this, in the first aspect, the present invention provides a method for preparing an electrode material for lithium extraction, comprising the following steps: mixing an electrode active material with a rare earth salt solution, and forming a rare earth phosphate layer on the surface of the electrode active material by in-situ coating; the electrode active material includes lithium iron phosphate and its doped derivatives.
[0038] It can be understood that the doped derivatives of lithium iron phosphate refer to the introduction of other elements into lithium iron phosphate (LiFePO4) materials to replace the original atoms such as lithium (Li), iron (Fe) or oxygen (O) to further improve the electrochemical properties of the electrode active material.
[0039] It should be noted that when the electrode active material is in contact with a rare earth salt solution, the rare earth ions react with the electrode active material to form a rare earth phosphate coating layer with lower solubility, thereby achieving in-situ coating of the surface of lithium iron phosphate and its doped derivatives with rare earth phosphate. The rare earth phosphate layer has excellent alkali resistance and stability, and can provide a reliable protective barrier for the electrode active material to prevent the electrode material from undergoing an undesirable phase change with the electrolyte.
[0040] Compared with the prior art, the present invention coats a layer of rare earth phosphate on the surface of the electrode active material particles by the method of "in-situ coating", which can significantly improve the cycle performance of the lithium extraction electrode (for example: capacity retention rate after multiple charge and discharge). Specifically, compared with the method of "mixing rare earth oxides with electrode active materials and then high-temperature heat treatment", the "in-situ coating" method provided by the present invention can significantly improve the density and uniformity of the rare earth phosphate coating layer and the bonding strength between the rare earth phosphate coating layer and the electrode active material, which helps to give full play to the physical barrier effect of the rare earth phosphate coating layer, and to avoid the electrode active material from contacting with salt lake brine (for example: alkaline carbonate brine) to the maximum extent, thereby reducing the possibility of phase change, so that the rare earth phosphate coating layer can effectively resist and avoid the decomposition of the electrode active material in salt lake brine (for example: alkaline carbonate brine), and achieve the purpose of long-term stable lithium extraction electrode. Therefore, the present invention has a significant advantage in improving the cycle performance of the lithium extraction electrode by the method of in-situ coating of rare earth phosphate, and can effectively solve the problem of fast capacity decay of the lithium extraction electrode used for alkaline solution in the prior art.
[0041] Preferably, before mixing the electrode active material with the rare earth salt solution, the method further comprises: mixing the electrode active material with a precursor solution containing a carbon source, and after solid-liquid separation, calcining the separated solid powder at high temperature under the protection of an inert gas, and then mixing the electrode active material coated with a carbon layer on the surface after high-temperature calcination with the rare earth salt solution, and forming a rare earth phosphate layer on the surface of the electrode active material coated with the carbon layer by in-situ coating; or,
[0042] After the rare earth phosphate layer is formed, the method further includes: mixing the electrode active material coated with the rare earth phosphate layer with a precursor solution containing a carbon source, and after solid-liquid separation, calcining the separated solid powder at high temperature under the protection of an inert gas.
[0043] Considering that the existing lithium extraction electrode has the problem of being difficult to balance the capacity retention rate and the lithium extraction rate when treating salt lake brine, especially alkaline brine (for example: carbonate type), the present invention prepares the electrode material for lithium extraction by in-situ coating of rare earth phosphate combined with carbon coating strategy, which can not only improve the cycle performance of the lithium extraction electrode, but also accelerate the lithium extraction rate by enhancing the conductivity of the lithium extraction electrode. Specifically, by in-situ coating of rare earth phosphate combined with carbon coating strategy, a three-layer sandwich structure with electrode active material as the core, rare earth phosphate layer and carbon layer as the shell is constructed, which can protect the core electrode active material and provide good ion and electron transmission channels at the same time, so as to balance better ion conductivity and electron conductivity, thereby improving the overall lithium extraction efficiency of the lithium extraction electrode, and ensuring the cycle stability of the lithium extraction electrode, so as to solve the problem that the lithium extraction electrode used for salt lake brine, especially alkaline brine (for example: carbonate type) in the prior art is difficult to balance the capacity retention rate and the lithium extraction rate. Among them, the rare earth phosphate layer can not only play a good physical barrier role for the electrode active material, but also improve the ionic conductivity of the electrode material, because rare earth elements can enhance the electrochemical activity of the electrode material, increase the migration rate of lithium ions in the electrode material, and thus accelerate the deintercalation of lithium ions. The carbon layer provides good electronic conductivity. The carbon material has high conductivity and can form a continuous electron transport network to ensure the rapid transmission of electrons in the electrode material.
[0044] The present invention prepares the electrode material for lithium extraction electrode by in-situ coating of rare earth phosphate combined with carbon coating strategy, which can effectively reduce the corrosion of salt lake brine, especially alkaline brine (such as carbonate type) on lithium extraction electrode, enhance the structural integrity and thermal stability of lithium extraction electrode, and significantly extend its cycle life. Compared with the prior art, the preparation method provided by the present invention can significantly reduce the replacement frequency of lithium extraction electrode, thereby showing obvious advantages in reducing overall cost. For example: the rare earth phosphate layer, as a physical isolation layer, can effectively isolate the electrode active material from the contact with salt lake brine, especially alkaline brine (such as carbonate type), thereby reducing and inhibiting the phase change on the surface of the electrode material. The application of the carbon layer also helps to improve the structural stability of the electrode material; during the working process of the lithium extraction electrode, the carbon layer can effectively absorb the stress caused by the volume change, reduce the formation of cracks, and thus extend the cycle life of the electrode material; in addition, the carbon layer also helps to enhance the thermal stability of the electrode material, further improving the electrochemical performance and reliability of the lithium extraction electrode.
[0045] In addition, the preparation method provided by the present invention realizes the coating of rare earth phosphate by in-situ phase transformation technology. This method is not only simple in process but also environmentally friendly, meeting the current needs of environmental protection and sustainable development. The promotion and application of this preparation method will help the application of electrochemical deintercalation method in lithium extraction from salt lake brine, especially alkaline brine (such as carbonate type), and promote its large-scale development.
[0046] In some preferred embodiments, the particle size of the electrode active material powder is 0.5-6.0 μm, the concentration of the rare earth salt solution is 0.02-3.5 mol / L; according to the solid-liquid ratio α and the mixing time t x , mixing the electrode active material with the rare earth salt solution, or mixing the electrode active material coated with a carbon layer after high temperature calcination with the rare earth salt solution, the solid-liquid ratio α is 1: (5-20), the mixing time t x 0.5-24h.
[0047] In some preferred embodiments, the concentration of the precursor solution containing the carbon source is 0.02-4 mol / L; according to the solid-liquid ratio δ and the mixing time t c , mixing the electrode active material with a precursor solution containing a carbon source, or mixing the electrode active material coated with a rare earth phosphate layer with a precursor solution containing a carbon source, wherein the solid-liquid ratio δ is 1:(5-20), and the mixing time t c 0.5-24h.
[0048] By selecting the above-mentioned synergistic particle size, the concentration of the rare earth salt solution, the concentration of the precursor solution containing the carbon source, and the solid-liquid ratio, a uniform and appropriately thick rare earth phosphate layer and a carbon layer can be obtained on the surface of the electrode active material per unit volume. The uniform and appropriately thick rare earth phosphate layer is conducive to giving full play to its physical barrier effect and effectively isolating salt lake brine, especially alkaline brine (such as carbonate type), thereby further improving the cycle stability of the lithium extraction electrode. At the same time, the uniform and appropriately thick rare earth phosphate layer and carbon layer are conducive to improving the conductivity of the electrode material and further improving the lithium extraction efficiency. Through the above-mentioned optimization measures, not only can the electrochemical performance of the lithium extraction electrode be improved, but also the overall cost can be reduced and the service life of the electrode can be extended while taking into account the economy and processability. For example, if the particle size is too large and / or the concentration of the coating liquid is too high and / or the solid-liquid ratio is too large, it is easy to cause the thickness of the coated rare earth phosphate layer and / or carbon layer to be uneven; if the particle size is too small and / or the concentration is too low, it is easy to cause the coated rare earth phosphate layer and / or carbon layer to be too thin and unable to effectively protect the electrode active material and / or achieve an improvement in lithium extraction efficiency, and if the solid-liquid ratio is too small, the economy is poor.
[0049] It can be understood that the solid-liquid ratio refers to the ratio of solid mass to liquid volume.
[0050] Exemplarily, the particle size of the electrode active material powder is 1.0μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm, 5.5μm; the concentration of the rare earth salt solution and / or the concentration of the precursor solution containing the carbon source is 0.05mol / L, 0.10mol / L, 0.50mol / L, 1.0mol / L, 1.5mol / L, 2.0mol / L, 2.5mol / L, 3.0mol / L, 3.5mol / L; the solid-liquid ratio α and / or the solid-liquid ratio δ is 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19.
[0051] More preferably, the particle size of the electrode active material powder is 1.0-3.0 μm; the solid-liquid ratio α and / or solid-liquid ratio δ is 1:(8-15); by carefully selecting a better particle size and solid-liquid ratio, a more uniform rare earth phosphate layer and a carbon layer with a more appropriate thickness can be obtained on the surface of the electrode active material per unit volume, which helps to further optimize the electrochemical properties of the electrode material, so that it can exhibit better cycle stability and lithium extraction efficiency and longer service life in the extraction of lithium from salt lake brine, especially alkaline brine (such as carbonate type).
[0052] Exemplarily, the mixing time t x and / or mixing time t c The mixing time is 1h, 5h, 10h, 15h and 20h. By controlling the mixing time (0.5-24h), it is possible to ensure that an appropriate amount of coating layer is formed on the surface of the electrode active material particles. This optimized coating mass fraction helps to further improve the cycle capacity retention rate and / or lithium extraction efficiency of the lithium extraction electrode.
[0053] In some preferred embodiments, the concentration of the rare earth salt solution is 0.2-2 mol / L, the solid-liquid ratio α is 1:(8-15), and the mixing time t x By selecting the above preferred concentration range (0.2-2 mol / L), solid-liquid ratio α (1:8-15) and mixing time t x(0.5-6h), the thickness and uniformity of the rare earth phosphate coating layer can be further optimized, so that the rare earth phosphate layer can effectively protect the electrode active material without significantly increasing the impedance. The appropriate concentration, solid-liquid ratio and mixing time can ensure the quality of the rare earth phosphate coating layer and the protective effect on the electrode active material while reducing the amount of rare earth salt used, achieving an optimal balance between cost and efficiency. Exemplarily, the concentration of the rare earth salt solution is 0.4mol / L, 0.6mol / L, 0.8mol / L, 1.0mol / L, 1.2mol / L, 1.4mol / L, 1.6mol / L, 1.8mol / L, and the mixing time is t x It is 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h.
[0054] When the electrode active material is mixed with a rare earth salt solution, or when the electrode active material coated with a carbon layer on the surface after high-temperature calcination is mixed with a rare earth salt solution, optionally, the mixing method includes one or a combination of ultrasonic dispersion and magnetic stirring; wherein the power of the ultrasonic dispersion is 100-500W, and the speed of the magnetic stirring is 50-800r / min. Exemplarily, the power of the ultrasonic dispersion is 150W, 200W, 250W, 300W, 350W, 400W, 450W, and the speed of the magnetic stirring is 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 600r / min, 700r / min.
[0055] For rare earth salt solutions, by selecting the above-mentioned ultrasonic dispersion power (100-500W) and / or rotation speed range (50-800r / min), the uniformity and thickness of the rare earth phosphate coating layer can be more accurately controlled. The formed rare earth phosphate coating layer can not only effectively protect the electrode active material from the erosion of salt lake brine, especially alkaline brine, but also achieve the best balance between efficiency and cost.
[0056] In one embodiment, the mixing method is ultrasonic dispersion, the power of the ultrasonic dispersion is 200-400W, and the time of ultrasonic dispersion is 3-5h.
[0057] In one embodiment, the mixing method is magnetic stirring, the rotation speed of the magnetic stirring is 200-500 r / min, and the stirring time is 3-6 h.
[0058] In one embodiment, the mixing method is specifically: ultrasonic dispersion is first performed, and then magnetic stirring is performed; wherein, the power of ultrasonic dispersion is 300-500W, and the dispersion time is 1-2h; the speed of magnetic stirring is 500-800r / min, and the stirring time is 1-2h.
[0059] It should be noted that the rare earth salt solution is an inorganic salt solution containing rare earth elements, and the inorganic salt solution is one or more of chloride, sulfate and nitrate.
[0060] Exemplarily, the rare earth elements include, but are not limited to, lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), gadolinium (Gd), dysprosium (Dy), yttrium (Y), and europium (Eu).
[0061] In some preferred embodiments, the concentration of the precursor solution containing the carbon source is 0.1-4 mol / L, the solid-liquid ratio δ is 1:(8-15), and the mixing time t c 1-24h; illustratively, the concentration of the precursor solution containing the carbon source is 0.3mol / L, 0.8mol / L, 1.2mol / L, 1.8mol / L, 2.2mol / L, 2.8mol / L, 3.2mol / L, 3.6mol / L, and the mixing time t c It is 4h, 8h, 12h, 16h and 20h.
[0062] For the precursor solution containing a carbon source, by selecting the above-mentioned preferred concentration range (0.1-4 mol / L), solid-liquid ratio δ (1:8-15) and mixing time t c (1-24h), which can ensure that a uniform and appropriately thick carbon layer is formed on the surface of the electrode active material particles or the surface of the rare earth phosphate layer coated thereon after high-temperature calcination. This uniform and appropriately thick carbon layer coating has a positive effect on improving the lithium extraction efficiency of the lithium extraction electrode and extending its cycle life.
[0063] When the electrode active material is mixed with a precursor solution containing a carbon source, or when the electrode active material coated with a rare earth phosphate layer on the surface is mixed with a precursor solution containing a carbon source, optionally, the mixing method includes but is not limited to stirring; the stirring speed is 50-800r / min, preferably 100-300r / min, and the stirring time is 3-8h. By more carefully controlling the rotation speed and time when the precursor solution containing the carbon source is mixed with the electrode active material or with the electrode active material coated with the rare earth phosphate layer, it is helpful to obtain a more uniform and suitable thickness of the carbon layer after high-temperature calcination, further improve the lithium extraction efficiency, cycle life and thermal stability of the lithium extraction electrode, and achieve an optimized balance between cost and efficiency. If the stirring speed is too low or the time is insufficient, the precursor containing the carbon source cannot be fully deposited on the surface of the electrode active material or the surface of the rare earth phosphate coating layer, affecting the uniformity and coating effect of the carbon layer finally formed. On the contrary, too high a rotation speed or too long a stirring time can easily lead to the redispersion of the deposited precursor containing the carbon source, reducing the uniformity and quality of the carbon layer finally formed, which is not conducive to further improving the electrochemical performance of the lithium extraction electrode. Therefore, appropriate stirring parameters are also important to ensure the performance of the lithium extraction electrode.
[0064] In some embodiments, the precursor solution containing a carbon source is a mixed solution of one or more of glucose, sucrose, dopamine, tannic acid, and polyvinyl pyrrolidone.
[0065] Specifically, for different types of precursor solutions containing carbon sources, by selecting the following preferred concentration ranges, their role in achieving effective carbon coating to improve the electrochemical performance of the lithium extraction electrode, including lithium extraction efficiency, cycle life and thermal stability, can be fully utilized, while taking into account both performance and cost-effectiveness;
[0066] (1) When the precursor solution containing a carbon source is a mixed solution of glucose and sucrose, the concentration of the mixed solution of glucose and sucrose is 1.0-4.0 mol / L, illustratively, the concentration of the mixed solution of glucose and sucrose is 1.3 mol / L, 1.7 mol / L, 2.0 mol / L, 2.3 mol / L, 2.7 mol / L, 3.0 mol / L, 3.3 mol / L, 3.7 mol / L; or,
[0067] (2) When the precursor solution containing a carbon source is a dopamine solution, the concentration of the dopamine solution is 0.1-0.3 mol / L. For example, the concentration of the dopamine solution is 0.15 mol / L, 0.20 mol / L, or 0.25 mol / L; or
[0068] (3) When the precursor solution containing a carbon source is a tannic acid solution, the concentration of the tannic acid solution is 0.2-1.0 mol / L. For example, the concentration of the tannic acid solution is 0.40 mol / L, 0.60 mol / L, or 0.80 mol / L; or
[0069] (4) When the precursor solution containing a carbon source is a polyvinyl pyrrolidone solution, the concentration of the polyvinyl pyrrolidone solution is 0.5-1.0 mol / L. Exemplarily, the concentration of the polyvinyl pyrrolidone solution is 0.6 mol / L, 0.75 mol / L, or 0.9 mol / L.
[0070] Preferably, the precursor solution containing the carbon source is a dopamine solution, which has a better bonding strength with the rare earth phosphate coating layer. From an economic point of view, it is preferred to use a mixed solution of glucose and sucrose as the precursor solution containing the carbon source.
[0071] In some embodiments, when dopamine and / or tannic acid are used as the precursor solution containing the carbon source, according to the solid-liquid ratio δ and the mixing time t c Before mixing, a buffer solution is added to adjust the pH value of the solution system to better maintain the stable polymerization of dopamine molecules and / or tannic acid molecules; specifically,
[0072] When dopamine is used for coating, the buffer solution is tris(hydroxymethylaminomethane) hydrochloride buffer salt with a pH of 8.5±0.2, i.e., HCl-tris solution;
[0073] When tannic acid is used for coating, the buffer solution is a 2,2-bis(hydroxymethyl)-2,2'2'-nitrilotriethanol solution with a pH of 7±0.2.
[0074] In some embodiments, the temperature of the high temperature calcination is 400-750°C, and the time of the high temperature calcination is 2-8h, which can ensure the phase stability and electrochemical properties of the electrode active material while achieving effective carbonization of the coating layer (i.e., the coating layer formed by the precursor solution containing the carbon source), thereby obtaining a lithium extraction electrode material with good alkali resistance and excellent electrochemical properties. Specifically, the lithium iron phosphate and its doped derivatives included in the electrode active material are prone to phase change at high temperatures to generate other impurity phases, which will affect the electrochemical properties and stability of the electrode material. In particular, when the temperature exceeds 750°C, lithium iron phosphate and its doped derivatives are prone to generate iron phosphide phases, which is an undesirable side reaction. Therefore, by controlling the calcination temperature within the range of 400-750°C, this phase change can be avoided, while promoting the carbonization reaction. The selection of the calcination time is also based on the appropriate degree of carbonization and ensuring phase stability. The calcination time of 2-8 hours can ensure that the carbonization reaction is fully carried out, while avoiding excessive calcination and causing the destruction of the structure of the coated electrode active material.
[0075] Illustratively, the high temperature calcination temperature is 450°C, 500°C, 550°C, 600°C, 650°C, 700°C; the high temperature calcination time is 7h, 6h, 5h, 4h, 3h.
[0076] Preferably, the high temperature calcination temperature is 550-700°C, and the high temperature calcination time is 2-8h.
[0077] It can be understood that high-temperature calcination under the protection of inert gas can prevent the oxidation of the electrode active material and the outer coated rare earth phosphate layer, thereby ensuring the stability of the electrode active material and the rare earth phosphate layer, and utilizing the stabilizing insulation effect of the uniform and complete rare earth phosphate coating layer to protect the electrode active material from decomposition during lithium extraction from salt lake brine, especially when treating highly alkaline brine (such as carbonate type), which can significantly improve the electrochemical properties and stability of the electrode material, such as: cycle capacity retention rate, lithium extraction efficiency.
[0078] Exemplarily, the inert gas includes, but is not limited to, nitrogen or argon, or a combination of both.
[0079] In some embodiments, the rare earth phosphate layer is coated first, and then the carbon layer is coated. After the rare earth phosphate layer is formed, the process further includes: performing a first solid-liquid separation to obtain an electrode active material with a rare earth phosphate layer coated on the surface, mixing the electrode active material with a rare earth phosphate layer coated on the surface with a precursor solution containing a carbon source, performing a second solid-liquid separation, and calcining the solid powder obtained by the second solid-liquid separation at a high temperature under the protection of an inert gas to obtain an electrode active material powder with a rare earth phosphate layer and a carbon layer coated on the surface. In this embodiment, preferably, the first solid-liquid separation specifically includes: obtaining an electrode active material with a rare earth phosphate layer coated on the surface by filtering and washing; specifically, separating the solid and liquid in the reaction system by filtering to collect the solid powder of the electrode active material with a rare earth phosphate layer coated on the surface, and then washing the collected solid powder to remove possible residual impurities and unreacted rare earth salt solution to better ensure good bonding between the rare earth phosphate layer and the carbon coating layer. Exemplarily, the electrode active material powder coated with a rare earth phosphate layer on the surface after filtration is washed 2 to 4 times with deionized water 5 to 10 times the mass of the solid powder. The second solid-liquid separation specifically includes: filtering and drying at 60-100°C. After filtration, the drying step is also one of the key links to ensure that the electrode active material maintains stability and optimizes the carbonization effect during high-temperature calcination. Before high-temperature calcination, removing excess water from the powder by drying helps prevent oxidation of the electrode active material and its rare earth phosphate coating during calcination, thereby ensuring its stability, because the presence of water easily promotes oxidation reactions, especially under high temperature conditions; and the stability of the electrode active material and its rare earth phosphate coating is conducive to improving the electrochemical properties and stability of the electrode material, such as: cycle capacity retention rate, lithium extraction efficiency.
[0080] In some embodiments, the carbon layer is coated first, and then the rare earth phosphate layer is coated. Before the electrode active material is mixed with the rare earth salt solution, it also includes: after the electrode active material is mixed with the precursor solution containing the carbon source, a first solid-liquid separation is performed, and the solid powder obtained by the first solid-liquid separation is subjected to high-temperature calcination under the protection of an inert gas; then the electrode active material coated with a carbon layer on the surface after high-temperature calcination is mixed with a rare earth salt solution, and a rare earth phosphate layer is formed on the surface of the electrode active material coated with the carbon layer by in-situ coating, and a second solid-liquid separation is performed to obtain an electrode active material powder coated with a carbon layer and a rare earth phosphate layer on the surface. It can be understood that the porous carbon layer allows the rare earth salt solution to contact and react with lithium iron phosphate to form a rare earth phosphate layer. In this embodiment, preferably, the first solid-liquid separation specifically includes: filtering and drying at 60-100°C; the second solid-liquid separation specifically includes: filtering and washing to obtain an electrode active material coated with a carbon layer and a rare earth phosphate layer on the surface.
[0081] Exemplarily, the drying temperature is 70°C, 80°C, or 90°C. The drying equipment includes, but is not limited to, an air drying oven. The drying time depends on the amount of solid powder to be dried, as long as excess moisture is removed.
[0082] In a second aspect, the present invention further provides an electrode material for lithium extraction, which is obtained by the preparation method described in the first aspect.
[0083] Specifically, the electrode material for lithium extraction is mainly composed of multiple core-shell structure units, the core of each unit is the electrode active material, and the surface of the electrode active material is sequentially coated with a rare earth phosphate layer and a carbon layer, or sequentially coated with a carbon layer and a rare earth phosphate layer.
[0084] In some embodiments, the thickness of the rare earth phosphate layer coated on the surface of the electrode active material is 5-20 nm, the thickness of the coated carbon layer is 3-50 nm, and the thickness of the interface fusion zone between the rare earth phosphate layer and the carbon layer is 1-3 nm.
[0085] In some embodiments, the particle size of the electrode active material at the core of each unit is 0.5-6.0 μm.
[0086] It should be noted that the units of the multiple core-shell structures can be independent of each other, or some or all of the units can be connected to form one or more sets.
[0087] In the third aspect, the present invention also provides a lithium extraction electrode, which is prepared using the electrode material described in the second aspect; the lithium extraction electrode is mainly used for extracting lithium from salt lake brine, and the salt lake brine includes carbonate brine, chloride brine, and sulfate brine.
[0088] In some embodiments, the preparation of the lithium extraction electrode mainly includes the following steps: mixing the electrode material obtained by the preparation method described in the first aspect or the electrode material described in the second aspect with polyvinylidene fluoride (PVDF) and superconducting carbon black (Super P), then adding NMP for slurry adjustment, coating the adjusted slurry on a metal mesh, and then vacuum drying to obtain a lithium extraction electrode (i.e., a lithium-rich lithium iron phosphate electrode).
[0089] In a fourth aspect, the present invention further provides a lithium extraction system, comprising an anode and a cathode, wherein the anode is an electrode prepared from the electrode material as described in the second aspect, and the cathode is an electrode prepared from the electrode material as described in the second aspect after a lithium removal treatment.
[0090] In some embodiments, the lithium extraction system includes an electrolysis device, the electrolysis device includes an anode and a cathode and an anion membrane, the anion membrane separates the electrolysis device into a cathode chamber and an anode chamber, the anode is located in the anode chamber, and the cathode is located in the cathode chamber; wherein the anode is the lithium extraction electrode as described in the third aspect (i.e., a lithium-rich lithium iron phosphate electrode), and the cathode is obtained by delithiation using the lithium extraction electrode as described in the third aspect.
[0091] Exemplarily, the delithiation mainly includes the following steps: using the lithium extraction electrode described in the third aspect (i.e., the lithium-rich lithium iron phosphate electrode) as the anode and the nickel foam electrode as the cathode, adding supporting electrolytes to the cathode chamber and the anode chamber of the electrolysis device respectively, and adjusting the pH value of the solution in the cathode chamber to 2-3, powering on for electrolysis, and the anode, i.e., the lithium-rich lithium iron phosphate electrode, is delithiated to obtain the cathode (lithium-deficient electrode).
[0092] The preparation method and the electrode material, lithium extraction electrode and lithium extraction system provided by the present invention achieve significant improvement in at least one of the cycle performance, lithium extraction efficiency and service life when applied to extract lithium from salt lake brine, especially alkaline brine.
[0093] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and comparative examples.
[0094] Example 1
[0095] This embodiment provides a method for preparing an electrode material for lithium extraction, comprising the following steps:
[0096] S1. Place 100 g of lithium iron phosphate powder with a particle size of 6.0 μm in a 0.02 mol / L lanthanum chloride solution (first coating solution) at a solid-liquid ratio α of 1:20, and magnetically stir at a speed of 50 r / min for 24 hours to form a lanthanum phosphate layer (i.e., the first coating layer) on the particle surface of the lithium iron phosphate powder; after stirring, collect the solid powder by filtration, and wash the collected solid powder three times with deionized water 5 times the amount of the solid powder, thereby obtaining lanthanum phosphate-coated lithium iron phosphate powder (i.e., electrode material for lithium extraction).
[0097] Example 2
[0098] The difference between this embodiment and embodiment 1 is that after step S1, step S2 is further included;
[0099] S2, take 80g of the obtained lanthanum phosphate-coated lithium iron phosphate powder, and place it in a dopamine solution (i.e., the second coating solution) with a concentration of 0.02mol / L according to a solid-liquid ratio δ of 1:20, wherein before adding the lanthanum phosphate-coated lithium iron phosphate powder, the dopamine solution has been adjusted to a pH of 8.3-8.5 using tris(hydroxymethylaminomethane) hydrochloride buffer salt (i.e., HCl-tris solution) with a pH of 8.5; magnetic stirring is performed at a speed of 50r / min for 24h; after the stirring is completed, the solid and liquid in the reaction system are separated by filtration, and a solid powder is collected to obtain a solid powder, and the collected solid powder is placed in a tubular furnace, argon is passed for protection, and then calcined at a high temperature of 400°C for 8h to obtain a lithium iron phosphate material (i.e., an electrode material for lithium extraction) having both a lanthanum phosphate coating layer and a carbon coating layer on the surface, such as Figure 4 (b) as shown.
[0100] Example 3
[0101] The difference between this embodiment and embodiment 2 is that: S1, 100g of lithium iron phosphate powder with a particle size of 0.5μm is placed in a 3.5mol / L lanthanum chloride solution (first coating liquid) at a solid-liquid ratio α of 1:5; S2, 80g of the obtained lanthanum phosphate-coated lithium iron phosphate powder is taken and placed in a dopamine solution with a concentration of 4mol / L (i.e., the second coating liquid) at a solid-liquid ratio δ of 1:5; the remaining steps and parameters are similar to those in embodiment 2.
[0102] Example 4
[0103] The difference between this embodiment and embodiment 2 is that carbon coating is performed first and then lithium iron phosphate coating is performed, specifically comprising: S1, placing 100 g of lithium iron phosphate powder with a particle size of 6.0 μm in a 0.02 mol / L dopamine solution (first coating solution) at a solid-liquid ratio δ of 1:20, wherein before adding the lithium iron phosphate powder, the dopamine solution has been adjusted to a pH of 8.3-8.5 using tris(hydroxymethylaminomethane) hydrochloride buffer salt (i.e., HCl-tris solution) with a pH of 8.5; magnetic stirring is performed at a speed of 50 r / min for 24 hours; after stirring, solid powder is collected by filtration, the collected solid powder is placed in a tubular furnace, argon is passed for protection, and then calcined at a high temperature of 400°C for 8 hours, thereby obtaining lithium iron phosphate powder with a surface coated with a carbon layer;
[0104] S2. Take 80g of the obtained lithium iron phosphate powder with a surface coated with a carbon layer, place it in a lanthanum chloride solution (second coating liquid) with a concentration of 0.02mol / L according to a solid-liquid ratio α of 1:20, and magnetically stir it at a speed of 50r / min for 24h. After the stirring is completed, the solid powder is collected by filtration, and the collected solid powder is washed 3 times with deionized water 5 times the amount of the solid powder to obtain a lithium iron phosphate material (i.e., an electrode material for lithium extraction) having both a carbon coating layer and a lanthanum phosphate coating layer on the surface.
[0105] Example 5
[0106] The difference between this embodiment and embodiment 2 is that the particle size of the lithium iron phosphate powder is 3.0 μm; the remaining steps and parameters are similar to those of embodiment 2.
[0107] Example 6
[0108] The difference between this embodiment and embodiment 2 is that the particle size of the lithium iron phosphate powder is 1.0 μm, and the remaining steps and parameters are similar to those of embodiment 2.
[0109] Example 7
[0110] The difference between this embodiment and embodiment 2 is that: S1, 100g of lithium iron phosphate powder with a particle size of 6.0μm is placed in a 2.0mol / L lanthanum chloride solution (first coating liquid) at a solid-liquid ratio α of 1:5; the remaining steps and parameters are similar to those in embodiment 2.
[0111] Example 8
[0112] The difference between this embodiment and embodiment 7 is that the concentration of lanthanum chloride solution is 1.0 mol / L; and the remaining steps and parameters are similar to those of embodiment 7.
[0113] Example 9
[0114] The difference between this embodiment and embodiment 7 is that the concentration of lanthanum chloride solution is 0.2 mol / L; and the remaining steps and parameters are similar to those of embodiment 7.
[0115] Example 10
[0116] The difference between this embodiment and embodiment 2 is that the solid-liquid ratio α is 1:15; the remaining steps and parameters are similar to those of embodiment 1.
[0117] Embodiment 11
[0118] The difference between this embodiment and embodiment 2 is that the solid-liquid ratio α is 1:12; the remaining steps and parameters are similar to those of embodiment 2.
[0119] Example 12
[0120] The difference between this embodiment and embodiment 2 is that the solid-liquid ratio α is 1:8; the remaining steps and parameters are similar to those of embodiment 2.
[0121] Embodiment 13
[0122] The difference between this embodiment and embodiment 2 is that the concentration of the dopamine solution is 0.1 mol / L, and the remaining steps and parameters are similar to those of embodiment 2.
[0123] Embodiment 14
[0124] The difference between this embodiment and embodiment 2 is that the concentration of the dopamine solution is 0.2 mol / L, and the remaining steps and parameters are similar to those of embodiment 2.
[0125] Embodiment 15
[0126] The difference between this embodiment and embodiment 2 is that the concentration of the dopamine solution is 0.3 mol / L, and the remaining steps and parameters are similar to those of embodiment 2.
[0127] Example 16
[0128] The difference between this embodiment and embodiment 2 is that the solid-liquid ratio δ is 1:8, and the remaining steps and parameters are similar to those of embodiment 2.
[0129] Embodiment 17
[0130] The difference between this embodiment and embodiment 2 is that the solid-liquid ratio δ is 1:15, and the remaining steps and parameters are similar to those of embodiment 2.
[0131] Embodiment 18
[0132] The difference between this embodiment and embodiment 2 is that in step S1, magnetic stirring is performed at a rotation speed of 200 r / min for 6 hours, and the remaining steps and parameters are similar to those in embodiment 2.
[0133] Embodiment 19
[0134] The difference between this embodiment and embodiment 2 is that in step S1, magnetic stirring is performed at a rotation speed of 500 r / min for 3 hours, and the remaining steps and parameters are similar to those in embodiment 2.
[0135] Embodiment 20
[0136] The difference between this embodiment and embodiment 2 is that: in step S1, magnetic stirring is performed at a rotation speed of 100 r / min for 24 hours; in step S2, magnetic stirring is performed at a rotation speed of 100 r / min for 8 hours, and the remaining steps and parameters are similar to those in embodiment 2.
[0137] Embodiment 21
[0138] The difference between this embodiment and embodiment 2 is that in step S2, the temperature of high temperature calcination is 750°C, and the remaining steps and parameters are similar to those of embodiment 2.
[0139] Embodiment 22
[0140] The difference between this embodiment and embodiment 2 is that: in step S1, magnetic stirring is performed at a rotation speed of 300 r / min for 5 hours, in step S2, magnetic stirring is performed at a rotation speed of 200 r / min for 6 hours, the high-temperature calcination temperature is 550°C, and the remaining steps and parameters are similar to those in embodiment 2.
[0141] Embodiment 23
[0142] The difference between this embodiment and embodiment 2 is that: in step S1, magnetic stirring is performed at a rotation speed of 400 / min for 4 hours, in step S2, magnetic stirring is performed at a rotation speed of 300r / min for 3 hours, the high-temperature calcination temperature is 700°C, and the remaining steps and parameters are similar to those in embodiment 2.
[0143] Embodiment 24
[0144] S1. Place 100 g of lithium iron phosphate powder with a particle size of 3.0 μm in a 0.2 mol / L Ce(NO3)3 solution (first coating solution) at a solid-liquid ratio α of 1:15, and stir magnetically at a speed of 200 r / min for 6 hours to form a cerium phosphate layer (i.e., the first coating layer) on the particle surface of the lithium iron phosphate powder; after stirring, collect the solid powder by filtration, and wash the collected solid powder three times with deionized water 5 times the amount of the solid powder, thereby obtaining lithium iron phosphate powder coated with cerium phosphate;
[0145] S2. Take 80g of the obtained cerium phosphate-coated lithium iron phosphate powder, and place it in a mixed solution of glucose + sucrose with a concentration of 1.0 mol / L (i.e., the second coating solution) according to a solid-liquid ratio δ of 1:15, wherein the concentration of glucose is 0.75 mol / L and the concentration of sucrose is 0.25 mol / L; stir magnetically at a speed of 200 r / min for 6 hours; after stirring, separate the solid and liquid in the reaction system by filtration, collect and obtain a solid powder, place the collected solid powder in a tubular furnace, pass argon gas for protection, and then calcine at a high temperature of 700°C for 7 hours to obtain a lithium iron phosphate material having both a cerium phosphate coating layer and a carbon coating layer on the surface (i.e., an electrode material for lithium extraction).
[0146] Embodiment 25
[0147] The difference between this embodiment and embodiment 24 is that in step S1, the lithium iron phosphate powder is replaced by Li 0.98 Mg 0.02FePO4 powder; in step S2, the concentration of the mixed solution of glucose + sucrose is 4.0 mol / L, wherein the concentration of glucose is 3.0 mol / L and the concentration of sucrose is 1.0 mol / L. The remaining steps and parameters are similar to those of Example 24.
[0148] Embodiment 26
[0149] The difference between this embodiment and Embodiment 24 is that: in step S1, the first coating liquid is a mixed solution of La2(SO4)3 and Eu2(SO4)3, wherein the concentration of La2(SO4)3 is 0.1 mol / L, and the concentration of Eu2(SO4)3 is 0.1 mol / L; in step S2, the second coating liquid is a 0.6 mol / L tannic acid solution, and the tannic acid solution has been adjusted to a pH of 6.8-7 using a 2,2-di(hydroxymethyl)-2,2'2'-nitrilotriethanol solution with a pH of 7; the remaining steps and parameters are similar to those of Embodiment 24.
[0150] Embodiment 27
[0151] The difference between this embodiment and Embodiment 24 is that: in step S1, the first coating liquid is a sulfate solution mixed with 7 rare earth elements as shown in Table 1; in step S2, the second coating liquid is a 0.75 mol / L polyvinyl pyrrolidone solution; and the remaining steps and parameters are similar to those of Embodiment 24.
[0152] Table 1 Composition of mixed rare earth sulfate solution / mg·L -1
[0153]
[0154] Comparative Example 1
[0155] The difference between this comparative example and Example 2 is that step S1 is omitted; the remaining steps S2 are similar to those of Example 2. The surface of the carbon-coated lithium iron phosphate particles obtained in Comparative Example 1 is as follows Figure 4 (a) shown.
[0156] Furthermore, the electrode materials obtained in the above-mentioned embodiments and comparative examples were used to prepare lithium extraction electrodes and the electrochemical performance tests were performed;
[0157] Specifically, the preparation of the lithium extraction electrode includes the following steps: mixing the electrode material obtained in any of the above embodiments or comparative examples with polyvinylidene fluoride (PVDF) and superconducting carbon black (Super P) at a ratio of 8:1:1, then adding NMP for slurry preparation, and then slurrying the prepared slurry at a temperature of 100 mg / cm 2 The coating density (calculated based on the coated electrode material contained in the homogenate) is applied on the titanium mesh, and the coating area is 15×20cm 2, and then vacuum drying at 100°C for 24 hours to obtain a lithium-extracted electrode (i.e., a lithium-rich lithium iron phosphate electrode).
[0158] Specifically, the electrochemical performance test includes:
[0159] (a) Lithium extraction efficiency performance test: The lithium extraction electrode prepared as above (i.e., lithium-rich lithium iron phosphate electrode) was used as the anode, the nickel foam electrode was used as the cathode, the anode and cathode were separated by an anion membrane, 5 g / L NaCl solution was added to the anode and cathode chambers as the supporting electrolyte, and the cathode was adjusted to a pH value of 2-3 with dilute sulfuric acid; electrolysis was performed at a cell voltage of 1.0 V. When the anode lithium de-ion current density was less than 2 A / m 2 The electrolysis process is terminated to obtain a lithium-deficient lithium iron phosphate electrode (obtained by delithiation of the lithium-rich lithium iron phosphate electrode).
[0160] Lithium extraction experiment: The electrolysis device was separated into a cathode chamber and an anode chamber by an anion membrane, and the lithium-rich lithium iron phosphate electrode and the lithium-deficient lithium iron phosphate electrode prepared above were placed in the anode chamber and the cathode chamber, respectively. 1.0L of carbonate brine to be treated was injected into the cathode chamber, and its composition was shown in Table 2 for the initial brine; 1.0L of 5g / L NaCl solution was injected into the anode chamber as a supporting electrolyte. Constant current electrolysis was performed at 600mA, and when the voltage reached 0.35V, it was switched to constant voltage electrolysis until the current was lower than 100mA to end the electrolysis process. The brine concentration at the end of the electrolysis was recorded, and its composition was shown in Table 2 for the ending brine; according to the Li element content X of the initial brine and the Li element content Y of the ending brine, For example, the lithium extraction efficiency of Example 2 = (1.02-0.1) / 1.02 = 90.2%. The lithium extraction efficiencies obtained by referring to the above test method for the other examples and comparative examples are shown in Tables 4 to 7.
[0161] Table 2: Composition of carbonate-type initial brine and final brine (g / L)
[0162] element Li Na K Mg Ca <![CDATA[SO4 2- ]]> <![CDATA[CO3 2- ]]> Initial brine 1.02 102.5 12.6 0.001 0.002 / 20.5 Example 2 End of brine 0.1 101.5 12.47 0.001 0.002 / 20.3
[0163] (b) Cyclic performance test: Repeat the lithium extraction experiment of (a) and record the cycling performance of the lithium extraction electrode, see Tables 4-7.
[0164] It can be understood that when 1.0 L of chloride brine to be treated is injected into the cathode chamber, lithium extraction experiments and cycle performance tests are carried out, and the results are shown in Table 3 and Figure 3 The electrochemical performance test results are shown.
[0165] Table 3: Composition of initial and final chloride-type brine (g / L)
[0166] element Li Na K Mg Ca <![CDATA[SO4 2- ]]> <![CDATA[CO3 2- ]]> Initial brine 0.98 102.5 12.6 10.1 1.5 2.75 / Example 2 End of brine 0.07 101.5 12.47 10.0 1.45 2.7 /
[0167] Further, in combination with Tables 4 to 7 and the accompanying drawings, the electrochemical performance results of the embodiments and comparative examples are analyzed as follows:
[0168] (1) From Tables 4 to 7 and Figure 1-2 It can be seen that compared with Comparative Example 1, under the same test conditions, the cycle capacity retention rate and lithium extraction efficiency of the embodiment of the present invention are significantly improved.
[0169] (2) It can be seen from Table 4 that compared with Example 2, the cycle capacity retention rate and lithium extraction efficiency of Examples 5 to 17 are slightly improved to varying degrees. It can be seen that by selecting the parameter range of raw materials and proportions provided in the preferred embodiment of the present invention, such as: particle size, rare earth salt solution concentration, solid-liquid ratio, and concentration of the precursor solution containing a carbon source, it is beneficial to further improve the cycle capacity retention rate and lithium extraction efficiency.
[0170] (3) It can be seen from Table 5 that compared with Example 2, the cycle capacity retention rate and lithium extraction efficiency of Examples 18 to 23 are also slightly improved to varying degrees. This shows that by selecting the process parameters provided in the preferred embodiment of the present invention, such as: the stirring speed and time after adding the rare earth salt solution, the stirring speed and time after adding the precursor solution containing the carbon source, and the temperature of the high-temperature calcination, it is beneficial to further improve the cycle capacity retention rate and lithium extraction efficiency.
[0171] (4) It can be seen from Table 6 that the method provided by the present invention can not only improve the cycle performance and lithium extraction efficiency of lithium iron phosphate, but also improve the cycle performance and lithium extraction efficiency of doped derivatives of lithium iron phosphate (such as Example 25), and from the combination of a variety of different coating solutions, excellent cycle capacity retention rate and lithium extraction efficiency can be obtained, indicating that the preparation method provided by the present invention has process feasibility.
[0172] (5) From Figure 3 As can be seen from Table 3, the preparation method provided by the present invention is not only applicable to the performance improvement of lithium extraction electrodes from carbonate brine, but also applicable to lithium extraction from other salt lake brines, such as Figure 3 In the lithium extraction from chloride-type brine shown in , the lithium extraction electrode obtained by the preparation method of the present invention also has excellent cycle performance and lithium extraction efficiency.
[0173] (6) It can be seen from Example 2 and Example 4 in Table 4 that the interchangeable carbon coating and rare earth phosphate coating sequence has little effect on the electrochemical performance of the lithium extraction electrode as a whole; thus, it can be seen that the present invention has significant anti-alkali corrosion performance by constructing a double-layer coating structure of a rare earth phosphate layer and a carbon layer, while also being able to well take into account the lithium ion transmission rate, thereby ensuring a high lithium extraction efficiency.
[0174] Table 4: Effects of raw material parameters and ratios on lithium extraction electrode performance under the same process conditions
[0175]
[0176]
[0177]
[0178] Table 5: Effect of different process conditions on the performance of lithium extraction electrodes with the same raw materials (same as Example 2)
[0179]
[0180]
[0181] Table 6: Effects of different electrode active materials and coating solutions on electrode performance under the same process conditions
[0182]
[0183]
[0184] Table 7: Comparison of Lithium Extraction Electrode Performance of Examples 1-2 and Comparative Example 1
[0185]
[0186] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing an electrode material for lithium extraction, characterized in that: The following steps are involved: The electrode active material is mixed with a rare earth salt solution, and a rare earth phosphate layer is formed on the surface of the electrode active material by in-situ coating; the electrode active material includes lithium iron phosphate and its doped derivatives.
2. The preparation method according to claim 1, characterized in that: After the rare earth phosphate layer is formed, the method further comprises: mixing the electrode active material having the rare earth phosphate layer coated on the surface with a precursor solution containing a carbon source, and after solid-liquid separation, calcining the separated solid powder at a high temperature under the protection of an inert gas; or Before mixing the electrode active material with the rare earth salt solution, the method also includes: mixing the electrode active material with a precursor solution containing a carbon source, and after solid-liquid separation, high-temperature calcining the separated solid powder under the protection of an inert gas; then mixing the electrode active material whose surface is coated with a carbon layer after high-temperature calcination with the rare earth salt solution, and forming a rare earth phosphate layer on the surface of the electrode active material coated with the carbon layer by in-situ coating.
3. The preparation method according to claim 1 or 2, characterized in that: The particle size of the electrode active material powder is 0.5-6.0 μm, and the concentration of the rare earth salt solution is 0.02-3.5 mol / L; According to the solid-liquid ratio α and mixing time t x , mixing the electrode active material with the rare earth salt solution, or mixing the electrode active material coated with a carbon layer after high temperature calcination with the rare earth salt solution, the solid-liquid ratio α is 1: (5-20), the mixing time t x 0.5-24h.
4. The preparation method according to claim 2, characterized in that: The concentration of the precursor solution containing the carbon source is 0.02-4 mol / L; according to the solid-liquid ratio δ and the mixing time t c , mixing the electrode active material with a precursor solution containing a carbon source, or mixing the electrode active material coated with a rare earth phosphate layer with a precursor solution containing a carbon source, wherein the solid-liquid ratio δ is 1:(5-20), and the mixing time t c 0.5-24h; and / or, The high temperature calcination temperature is 400-750°C, and the high temperature calcination time is 2-8h.
5. The preparation method according to claim 3, characterized in that: The concentration of the rare earth salt solution is 0.2-2 mol / L, the solid-liquid ratio α is 1:(8-15), and the mixing time t x 0.5-6h.
6. The preparation method according to claim 2, characterized in that: The rare earth salt solution is an inorganic salt solution containing rare earth elements, and the inorganic salt solution is one or more of chloride, sulfate and nitrate; and / or, The precursor solution containing the carbon source is a mixed solution of one or more of glucose, sucrose, dopamine, tannic acid and polyvinyl pyrrolidone.
7. The preparation method according to claim 6, characterized in that: When the precursor solution containing the carbon source is a mixed solution of glucose and sucrose, the concentration of the mixed solution of glucose and sucrose is 1.0-4.0 mol / L; or, When the precursor solution containing a carbon source is a dopamine solution, the concentration of the dopamine solution is 0.1-0.3 mol / L; or, When the precursor solution containing the carbon source is a tannic acid solution, the concentration of the tannic acid solution is 0.2-1.0 mol / L; or, When the precursor solution containing the carbon source is a polyvinyl pyrrolidone solution, the concentration of the polyvinyl pyrrolidone solution is 0.5-1.0 mol / L.
8. An electrode material for lithium extraction, characterized in that: The method is adopted as claimed in any one of claims 1 to 7.
9. A lithium extraction electrode, characterized in that: The electrode material according to claim 8 is used for preparing the lithium extraction electrode; the lithium extraction electrode is mainly used for extracting lithium from salt lake brine, and the salt lake brine includes carbonate brine, chloride brine, and sulfate brine.
10. A lithium extraction system, characterized in that: It comprises an anode and a cathode, wherein the anode is an electrode prepared from the electrode material as claimed in claim 8, and the cathode is an electrode prepared from the electrode material as claimed in claim 8 after delithiation treatment.
Citation Information
Cited By
Method for extracting lithium by using lithium ion battery electrode material original halide
CN120366596A
Carbon-coated lithium iron phosphate material, preparation method and application thereof
CN120453359A